The impact of using creative strategies in media messages on public relations departments performance in government institutions - Tharwat, Wafaa Abdel Khalek; Abdelhay, Sameh; Draz, Ahed Maher Abu; Salem, Omnia Mohamed Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
The study aims to measure the impact of implementing creative strategies in government institutions’ media messages on the public’s perception of the content. It is a descriptive study. It relied on survey methodology, using two sides, descriptive and analytical ones, and within its framework, a field survey was used on a sample of the public to verify the study’s hypotheses, answer its questions, and draw significant results. The results show that public relations departments in government institutions employ a high level of creative strategies in their media messages. Institutions are usually keen to attract the public’s attention, influence it, achieve the highest comprehension rates of their message content, and convince them through several methods, including employing creativity strategies. The results also reflect the diversity of strategies used in media messages of the Emirati government institutions, topped by the strategy of stimulating public interaction with digital content, then the strategy of providing information, creative solutions, and evidence, and the strategy of organizing virtual initiatives, competitions, and events, and the results showed a significant positive relationship between the use of creative strategies and the public’s understanding of the content. Creativity in the media message is the institution’s basic foundation. Creativity’s role lies in its ability to present new ideas in integrated contexts, thus achieving the government institutions’ performance goals by meeting the customers’ needs. Creative media creates a link between the institution and the target public.